Evaluation of genetically inactivated alpha toxin for protection in multiple mouse models of Staphylococcus aureus infection. - Rebecca A Brady; Christopher P Mocca; Ranjani Prabhakara; Roger D Plaut; Mark E Shirtliff; Tod J Merkel; Drusilla L Burns (PLoS ONE)
Staphylococcus aureus is a major human pathogen and a leading cause of nosocomial and community-acquired infections. Development of a vaccine against this pathogen is an important goal. While S. aureus protective antigens have been identified in the literature, the majority have only been tested in a single animal model of disease. We wished to evaluate the ability of one S. aureus vaccine antigen to protect in multiple mouse models, thus assessing whether protection in one model translates to protection in other models encompassing the full breadth of infections the pathogen can cause. We chose to focus on genetically inactivated alpha toxin mutant HlaH35L. We evaluated the protection afforded by this antigen in three models of infection using the same vaccine dose, regimen, route of immunization, adjuvant, and challenge strain. When mice were immunized with HlaH35L and challenged via a skin and soft tissue infection model, HlaH35L immunization led to a less severe infection and decreased S. aureus levels at the challenge site when compared to controls. Challenge of HlaH35L-immunized mice using a systemic infection model resulted in a limited, but statistically significant decrease in bacterial colonization as compared to that observed with control mice. In contrast, in a prosthetic implant model of chronic biofilm infection, there was no significant difference in bacterial levels when compared to controls. These results demonstrate that vaccines may confer protection against one form of S. aureus disease without conferring protection against other disease presentations and thus underscore a significant challenge in S. aureus vaccine development.